Unit cell and battery cell including the same
The use of a copolymer and rosin ester-based additive in the adhesive composition for unit cells addresses positioning and adhesive strength issues in battery manufacturing, enhancing the integrity and reliability of the battery cells.
Patent Information
- Application Number
- JP2023545871
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-04-19
- Filing Date
- 2022-04-27
- Publication Date
- 2025-04-02
- Estimated Expiration
- 2042-04-27
AI Technical Summary
Conventional methods for manufacturing unit cells in secondary batteries face issues such as electrodes being pushed out of position or damaged due to uneven heating and pressure, leading to variations in adhesive strength between electrodes and separators.
A unit cell design using an adhesive composition comprising a copolymer and a rosin ester-based additive, applied to separators and electrodes, to enhance bonding and minimize heat and pressure during lamination, ensuring uniform adhesive strength.
The adhesive composition prevents deformation and damage of electrodes and separators, reducing defective rates in battery cells by maintaining consistent adhesive force.
Smart Images

Figure 0007654934000015 
Figure 0007654934000016 
Figure 0007654934000017
Abstract
Description
[Technical field]
[0001] Cross-reference to related applications This application claims the benefit of priority based on Korean Patent Application No. 10-2021-0076219 dated June 11, 2021, Korean Patent Application No. 10-2021-0076220 dated June 11, 2021, and Korean Patent Application No. 10-2022-0048385 dated April 19, 2022, and all contents disclosed in the documents of said Korean patent applications are incorporated herein by reference.
[0002] The present invention relates to a unit cell and a battery cell including the same, and more particularly, to a unit cell including an adhesive composition that can be used in manufacturing an electrode assembly of a secondary battery, and a battery cell including the same. [Background technology]
[0003] In modern society, as the use of portable devices such as mobile phones, notebook computers, camcorders, and digital cameras has become commonplace, there has been active development of technology related to such mobile devices. In addition, rechargeable secondary batteries are a solution to address air pollution caused by existing gasoline-powered vehicles that use fossil fuels, and are used as the power source for electric vehicles (EVs), hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (P-HEVs), etc., so there is an increasing need for the development of secondary batteries.
[0004] Currently commercially available secondary batteries include nickel-cadmium batteries, nickel-metal hydride batteries, nickel-zinc batteries, and lithium secondary batteries. Of these, lithium secondary batteries are in the spotlight due to their advantages of being freely chargeable and dischargeable, having a very low self-discharge rate, and having a high energy density.
[0005] Such lithium secondary batteries mainly use lithium-based oxides and carbon materials as positive and negative active materials, respectively, and include an electrode assembly in which a positive electrode plate and a negative electrode plate, on which the positive and negative active materials are applied, are arranged with a separator sandwiched therebetween, and an exterior material, i.e., a battery case, that hermetically houses the electrode assembly together with an electrolyte.
[0006] Depending on the shape of the battery case, secondary batteries are classified into cylindrical batteries and prismatic batteries, in which the electrode assembly is housed inside a cylindrical or prismatic metal can, and pouch batteries, in which the electrode assembly is housed inside a pouch-type case made of an aluminum laminate sheet.
[0007] Meanwhile, the electrode assembly can be manufactured in various ways, but in general, the unit cells 4 are manufactured in advance and then a plurality of the unit cells 4 are stacked to manufacture the electrode assembly.
[0008] FIG. 1 is a simplified diagram illustrating how a unit cell is manufactured by a conventional method.
[0009] Referring to FIG. 1, in a conventional manufacturing method for manufacturing a unit cell 4, a positive electrode 1, a separator 3 stacked relatively above, a negative electrode 2, and a separator 3 stacked relatively below are wound in a roll shape and continuously unwound and supplied.
[0010] At this time, the separator 3 is continuously supplied, the negative electrode 2 is supplied between the separators 3, and the positive electrode 1 is supplied on the upper separator 3 and cut to a predetermined size and then input at a certain interval. At this time, the input time is controlled so that the negative electrode 2 and the positive electrode 1 are stacked up and down corresponding to each other. Therefore, the separator 3 is continuously connected, and the negative electrode 2 and the positive electrode 1 pass through the laminating device continuously with a certain distance between the adjacent negative electrode 2 and positive electrode 1.
[0011] While passing through the laminating device, the positive electrode 1, the separator 3, and the negative electrode 2 are heated and pressed by nip rollers 5. That is, after lamination (bonding) is performed by heating and pressing, the separator 3 is cut to produce individual unit cells 4.
[0012] However, the conventional method described above has problems in that the electrodes (negative and positive electrodes) may be pushed out of their original positions or damaged when heat and pressure are applied, and if the heating is not uniform, differences in the adhesive strength between the electrodes (positive electrode 1, negative electrode 2) and the separator 3 may occur. Summary of the Invention [Problem to be solved by the invention]
[0013] An object of the present invention is to provide a unit cell including an adhesive composition capable of reducing the defective rate of a final battery cell by eliminating the adhesive force between an electrode and a separator included in an electrode assembly, and a battery cell including the same.
[0014] However, the problems to be solved by the embodiments of the present invention are not limited to the above problems, and can be variously expanded within the scope of the technical ideas included in the present invention. [Means for solving the problem]
[0015] According to an embodiment of the present invention, a unit cell is a unit cell in which separators and electrodes are alternately stacked, and a lower separator, a first electrode, an upper separator, and a second electrode are stacked in this order. An adhesive is applied to one side of at least one of the electrode and the separator to bond the electrode and the separator or the lower separator and the upper separator. The adhesive comprises an adhesive composition including a copolymer and a rosin ester-based additive. The copolymer comprises 60.1 to 79.9 wt % of two or more alkyl (meth)acrylate repeating units (A) and 20.1 to 39.9 wt % of (meth)acrylate repeating units having a terminal hydroxyl group (B). The adhesive composition comprises 30 to 70 wt % of the copolymer and 30 to 70 wt % of the additive.
[0016] The adhesive may be applied to one surface of the upper separation film or the lower separation film to bond the upper separation film and the lower separation film.
[0017] The adhesive may be applied to one surface of the separator or the electrode to bond the separator and the electrode facing each other.
[0018] The repeating unit (A) can be represented by the following Chemical Formula 1, and the repeating unit (B) can be represented by the following Chemical Formula 2. [Chemical formula 1] [ka] In the above chemical formula 1, R1 is a hydrogen atom or a methyl group, R2 is a straight-chain or branched-chain alkyl group having 1 to 12 carbon atoms, and n is the repeating number of the repeating unit (A) and is an integer of 450 to 850. [Chemical formula 2] [ka] In the above chemical formula 2, R3 is a hydrogen atom or a methyl group, R4 is a straight-chain or branched-chain alkyl group having 1 to 9 carbon atoms to which a hydroxyl group is bonded, and m is the repeating number of the repeating unit (B) and is an integer of 200 to 350.
[0019] The weight average molecular weight (Mw) of the copolymer may be 120,000 to 140,000.
[0020] The two or more repeating units (A) include at least one acrylate repeating unit and at least one other methacrylate repeating unit, and an alkyl group having a larger carbon number than that of the methacrylate repeating unit may be bonded to the terminal of the acrylate repeating unit.
[0021] The acrylate repeating unit may have a straight or branched alkyl group having 4 to 12 carbon atoms bonded to its terminal, and the methacrylate repeating unit may have an alkyl group having 1 to 3 carbon atoms bonded to its terminal.
[0022] The two or more repeating units (A) may all be acrylate repeating units, and at least one of the repeating units (A) may be an isobornyl acrylate repeating unit.
[0023] The two or more repeating units (A) may include a methyl methacrylate repeating unit and a 2-ethylhexyl acrylate (2-EHA) repeating unit.
[0024] The repeating unit (B) may include a 2-hydroxyethyl acrylate (2-HEA) repeating unit.
[0025] The additive may have a glass transition temperature (Tg) of -10 degrees Celsius or lower.
[0026] The HSP (hilderbrand solubility) of the additive is 19 to 22 (MPa). 0.5 can have a value of
[0027] The adhesive composition may contain 30% to 50% by weight of the copolymer and 50% to 70% by weight of the additive.
[0028] The adhesive composition may have a glass transition temperature of -40 degrees Celsius or lower.
[0029] The adhesive composition may have a glass transition temperature of -50 degrees Celsius or lower.
[0030] The adhesive composition may have a viscosity of 2200 cPs to 2500 cPs at 80°C.
[0031] The adhesive composition may have a viscosity of 2200 cPs to 2400 cPs at 80°C.
[0032] When the adhesive composition is discharged from a dispenser at a first time point to form a dot, the dot has a first diameter value, and when the adhesive composition is discharged from the dispenser at a second time point that is 30 minutes or more after the first time point to form a dot, the deviation between the first diameter and the second diameter may be within 5%, and the temperature of the dispenser may be 120°C.
[0033] The adhesive strength of the adhesive composition is 40 gf / mm 2 It may be more than that.
[0034] The adhesive strength of the adhesive composition is 85 to 92 gf / mm 2 may be also possible.
[0035] According to another embodiment of the present invention, in an electrode assembly formed by alternately stacking the unit cells, an adhesive for adhering the electrodes and the separator includes an adhesive pattern disposed at the same position between each of the electrodes and the separator.
[0036] According to another embodiment of the present invention, in an electrode assembly formed by alternately stacking the unit cells, an adhesive for bonding the electrodes and the separators includes adhesive patterns arranged in an alternating pattern between the electrodes and the separators.
[0037] A battery cell according to still another embodiment of the present invention includes the above-described unit cell.
[0038] The battery cell may have a zigzag shape due to the separator being folded. Effect of the Invention
[0039] According to an embodiment, an adhesive composition is provided between an electrode and a separator or between two separators during a process of manufacturing an electrode assembly, so that heat and pressure applied when lamination is performed between the electrode and the separator can be minimized, and deviation between the separator and the electrode can be prevented, thereby preventing deformation and damage of the electrode and the separator.
[0040] The effects of the present invention are not limited to those mentioned above, and other effects not mentioned will be clearly understood by those skilled in the art from the description of the claims. [Brief description of the drawings]
[0041] [Figure 1] 1 is a simplified diagram illustrating a process for manufacturing a unit cell according to a conventional method; [Diagram 2] FIG. 2 is a diagram for explaining a method for measuring the adhesive strength of an adhesive composition according to one embodiment of the present invention. [Diagram 3] FIG. 2 is a graph showing the Linear Sweep Voltammetry (LSV) of an adhesive composition according to one embodiment of the present invention. [Figure 4] 1 is a diagram illustrating an example in which an adhesive composition according to an embodiment of the present invention is used in a process for manufacturing an electrode assembly. [Diagram 5]10A and 10B are diagrams illustrating another example in which an adhesive composition according to an embodiment of the present invention is used in a process for manufacturing an electrode assembly. [Figure 6] FIG. 2 illustrates a unit cell including an adhesive composition according to one embodiment of the present invention. [Figure 7] 1 is a diagram illustrating an example of an area where an adhesive is applied in a unit cell including an adhesive composition according to one embodiment of the present invention. [Figure 8] FIG. 6 is a diagram showing an adhesive being applied to the electrode or separator of FIG. 5. [Figure 9] FIG. 6 is a diagram showing an adhesive being applied to the electrode or separator of FIG. 5. [Figure 10] FIG. 6 is a diagram showing an adhesive being applied to the electrode or separator of FIG. 5. [Figure 11] 1 is a graph showing a capacity measured in a battery cell according to an embodiment of the present invention. [Figure 12] 4 is a graph showing resistance values measured in a battery cell according to an embodiment of the present invention. [Figure 13] 1 is a graph showing capacity retention measured in a battery cell according to an embodiment of the present invention. [Figure 14] 4 is a cross-sectional view showing an electrode assembly according to another embodiment of the present invention. [Figure 15] 4 is a cross-sectional view showing an electrode assembly according to still another embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0042] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will now be described in detail with reference to the accompanying drawings, in which: FIG. 1 is a block diagram of a semiconductor device according to an embodiment of the present invention;
[0043] The present invention relates to an adhesive composition.
[0044] In this application, 'adhesive composition' may refer to a composition that can act as an adhesive before or after crosslinking or curing. The definition of adhesive is as defined in the art.
[0045] In this application, an 'adhesive (co)polymer' refers to a polymer whose physical properties, such as glass transition temperature, are adjusted so that adhesive properties are exhibited before and / or after crosslinking or curing. The composition of such polymers is well known in the art.
[0046] The adhesive composition may include an adhesive (co)polymer. When the composition is in a solution state containing water or an organic solvent, the ratio of the adhesive (co)polymer may be based on the weight of the solid content excluding the solvent.
[0047] In this application, "acrylic (co)polymer" refers to a (co)polymer containing, as a main component, a polymerized unit or a repeating unit derived from one or more acrylic monomers. In this application, a polymerized unit or a repeating unit of a certain monomer refers to a unit structure derived from the monomer and contained in the (co)polymer after undergoing a polymerization reaction.
[0048] In the present application, when a certain component B contains another component A as a main component, it can mean that the ratio of the component A in the component B is about 55% by weight or more, 60% by weight or more, 65% by weight or more, 70% by weight or more, 75% by weight or more, 80% by weight or more, 85% by weight or more, or 90% by weight or more based on the total weight of B. The upper limit of the ratio is not particularly limited, and may be, for example, about 98% by weight or less or 95% by weight or less.
[0049] In this application, "acrylic monomer" refers to acrylic acid or methacrylic acid, or a derivative thereof, such as an acrylate or methacrylate ester, and "(meth)acrylic" refers to acrylic or methacrylic.
[0050] The acrylic polymer may be an adhesive polymer having adhesive properties.
[0051] The acrylic polymer may contain polymerized units of an alkyl (meth)acrylate monomer. The acrylic polymer may contain repeating units (A) derived from an alkyl (meth)acrylate monomer.
[0052] In one example, the repeating unit (A) may be a compound represented by the following formula 1: [Chemical formula 1] [ka] In the above chemical formula 1, R1 is a hydrogen atom or a methyl group, R2 is a straight-chain or branched-chain alkyl group having 1 to 12 carbon atoms, and n is the repeating number of the repeating unit (A) and is an integer of 450 to 850.
[0053] The repeating unit (A) contained in the acrylic polymer may be derived from an alkyl (meth)acrylate monomer having an alkyl group having 1 to 12 carbon atoms. Here, the alkyl group may be linear or branched. Specific examples of the alkyl (meth)acrylate monomer include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, t-butyl (meth)acrylate, sec-butyl (meth)acrylate, pentyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, 2-ethylbutyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate and / or lauryl (meth)acrylate. The alkyl (meth)acrylate monomer may be selected in consideration of the cohesive strength, glass transition temperature, and adhesion of the final adhesive composition.
[0054] The acrylic polymer may further include a repeating unit of a copolymerizable monomer having a polar functional group as an additional polymerization unit to improve cohesive strength, etc. The copolymerizable monomer having a polar functional group may mean a monomer that can be copolymerized with a compound that forms an acrylic polymer, such as the above-mentioned alkyl (meth)acrylate monomer. In addition, the copolymerizable monomer having a polar functional group may mean a monomer that can provide a polar functional group to a side chain or end of the polymer after being copolymerized to form an acrylic polymer. The polar functional group may be, for example, a functional group that can react with a crosslinking agent described below by application of heat to realize a crosslinked structure or that can play a role in improving the wettability of the adhesive layer. Examples of the polar functional group include, for example, a hydroxyl group, a carboxyl group or its anhydride group, an acid group such as a sulfonic acid group or a phosphoric acid group, a glycidyl group, an amino group, or an isocyanate group.
[0055] The acrylic polymer may contain polymerized units of an alkyl (meth)acrylate monomer having a hydroxy group. The acrylic polymer may contain repeating units (B) derived from a (meth)acrylate monomer having a hydroxy group.
[0056] In one example, the repeating unit (B) may be a compound represented by the following formula 2: [Chemical formula 2] [ka] In the above chemical formula 2, R3 is a hydrogen atom or a methyl group, R4 is a straight-chain or branched-chain alkyl group having 1 to 9 carbon atoms to which a hydroxyl group is bonded, and m is the repeating number of the repeating unit (B) and is an integer of 200 to 350.
[0057] The (meth)acrylate monomer having a hydroxy group may be a monomer that contains both a site capable of copolymerizing with other monomers that form an acrylic polymer and a hydroxy group, and can provide a hydroxy group to the acrylic polymer after polymerization. The hydroxyalkyl (meth)acrylate monomer may contain a hydroxyalkyl group having 1 to 9 carbon atoms. Examples of such monomers include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 7-hydroxyheptyl (meth)acrylate, and 8-hydroxyoctyl (meth)acrylate.
[0058] The acrylic polymer may be a terpolymer formed through copolymerization of three kinds of acrylic monomers. Here, two of the three monomers may be alkyl (meth)acrylates, and the other may be a (meth)acrylate having a hydroxyl group. The terpolymer may contain two kinds of (meth)acrylate repeating units (A) and one kind of (meth)acrylate repeating unit (B) containing a hydroxyl group. Here, (meth)acrylate may mean derived from a (meth)acrylate monomer.
[0059] In one embodiment, the terpolymer may be a compound represented by the following formula 3: [Chemical formula 3] [ka] In the above formula 3, each repeating unit may be the repeating unit (A) or the repeating unit (B) described above. 1a , R 1b and R3 is a hydrogen atom or a methyl group, R 2a and R 2b is a straight or branched alkyl group having 1 to 12 carbon atoms, and R4 is a straight or branched alkyl group having 1 to 9 carbon atoms to which a hydroxyl group is bonded. a and n b is the number of repetitions, na and n b are each an integer from 450 to 850, and m is the number of repetitions and is an integer from 200 to 350.
[0060] In addition, in a terpolymer containing two or more kinds of repeating units (A) and repeating units (B), the coefficient ratio of the repeating units (A) and (B) can be provided in various ways. For example, the coefficient ratio of the repeating units (A) and (B) may be 80 / 20 to 70 / 30.
[0061] The repeating unit (A) and the repeating unit (B) contained in the acrylic polymer may be selected from any of the above examples, but may need to be appropriately selected in consideration of the rigidity or adhesive performance of the final polymer.
[0062] Specifically, acrylic polymers may be adhesive polymers, and adhesive polymers may exhibit different adhesive power or strength depending on the monomer. The glass transition temperature of a monomer may be different depending on the carbon number or structure of the alkyl group contained in the monomer, and therefore the adhesive performance of the polymer may be different. In addition, the fluidity of a polymer may decrease / increase depending on the length or structure of the alkyl chain, so the peel and shear strength of the polymer may be affected by the alkyl group contained in the monomer.
[0063] Generally, to impart strength to the adhesive polymer, methacrylate monomers are preferred over acrylate monomers, and a specific example is methyl methacrylate (MMA). To impart flexibility to the adhesive polymer, the use of short chain lengths such as methyl acrylate (MA), ethyl acrylate (EA) or 2-ethylhexyl acrylate (2-EHA) can be considered. Meanwhile, (meth)acrylates containing hydroxyl groups can improve the crosslinking or wettability of the adhesive polymer, so the viscosity can be increased by including hydroxyl (meth)acrylates in the polymer.
[0064] For example, one of the two repeating units (A) contained in the acrylic polymer may be an alkyl acrylate type, and the other may be an alkyl methacrylate type. In this case, an alkyl group having a carbon number greater than that of the methacrylate type repeating unit may be bonded to the end of the acrylate type repeating unit. For example, a linear or branched alkyl group having 4 to 12 carbon atoms may be bonded to the end of the acrylate type repeating unit, and an alkyl group having 1 to 3 carbon atoms may be bonded to the end of the methacrylate type repeating unit. This may be because methacrylate is stronger and harder than acrylate. This may be because when an alkyl group having a long chain length is bonded to a high-strength methacrylate type repeating unit, the resistance to external stress such as peeling and shear strength may be weakened due to a decrease in fluidity.
[0065] As another example, when both of the two repeating units (A) contained in the acrylic polymer are acrylate-based, at least one of the repeating units (A) may contain an alkyl group having 6 or more carbon atoms or an alkyl group having 10 or more carbon atoms. More specifically, when both of the repeating units (A) are acrylate-based, at least one of the repeating units (A) may be derived from isobornyl acetate (IBoA). This may be to ensure the rigidity of the final polymer.
[0066] The acrylic polymer may contain 40 to 90 parts by weight of the two repeating units (A) and 10 to 60 parts by weight of the repeating unit (B) relative to 100 parts by weight of the polymer. The acrylic polymer may contain 50 to 80 parts by weight of the repeating unit (A) and 20 to 50 parts by weight of the repeating unit (B) relative to 100 parts by weight of the polymer. The ratio may be changed in consideration of the desired cohesive force, wettability, etc. In this case, the ratio may be based on the case where the acrylic polymer contains only the repeating units described above, or may be excluding the solvent or other substances. That is, the total of the repeating units may be 100 parts by weight.
[0067] As the acrylic polymer, for example, a polymer having a weight average molecular weight (Mw) of 90,000 to 150,000, 110,000 to 140,000, or 120,000 to 130,000 can be used. If the molecular weight of the acrylic polymer is 90,000 or less, the adhesive force (adhesive force between the adhesive and the interface) may decrease, and if the molecular weight is 150,000 or more, there is a problem of a decrease in the durability (cohesive force) of the adhesive polymer and a decrease in stability during dispenser discharge due to an increase in viscosity.
[0068] Meanwhile, in the present specification, the molecular weight of the adhesive composition can be measured by a conventional method known in the art. Conventional molecular weight measurements can be performed by a terminal group quantitative method that quantitatively analyzes functional groups at the molecular chain end to determine the molecular weight, a general method (separation membrane permeation method, vapor pressure osmometry, etc.) using physical properties such as osmotic pressure, vapor pressure depression, boiling point elevation, freezing point depression, etc., a light scattering method that uses light scattering, an ultracentrifugation method that measures the molecular weight by analyzing the sedimentation rate or concentration distribution after centrifuging a polymer solution, a viscosimetry that uses the viscosity of the polymer solution, gel permeation chromatography (GPC) using high performance liquid chromatography (HPLC), etc., or other methods. In the present specification, "molecular weight" can mean "weight average molecular weight".
[0069] The adhesive strength of acrylic polymer is 15-20gf / mm 2 or 25 gf / mm 2 It is preferable that the adhesive strength is equal to or more than the above range. This is because, if the adhesive strength is less than the above range, the objects to be adhered may easily peel off. When an acrylic polymer is used in a process for manufacturing an electrode assembly as described below, the acrylic polymer must at least satisfy the above range in order to adequately fix the electrode and the separator.
[0070] The viscosity of the acrylic polymer may be preferably 4000 cPs or less or 3500 cPs or less at 80° C. This may be to allow the adhesive composition containing the acrylic polymer to be discharged in a uniform size when it is sprayed through a spraying device. At this time, the temperature of the spraying device during the discharge may be 100° C. to 150° C., preferably 120° C.
[0071] The acrylic polymer can be prepared by a known polymerization method. For example, the above-mentioned alkyl (meth)acrylate monomer and polar group-containing copolymerizable monomer and / or other comonomers are appropriately mixed in a desired weight ratio to prepare a monomer mixture, which can be applied to a conventional polymerization method such as solution polymerization, photo polymerization, bulk polymerization, suspension polymerization, or emulsion polymerization to prepare an acrylic polymer. In this case, the polymerization temperature and polymerization time can be arbitrarily selected depending on the polymerization method and the type of polymerization initiator used. For example, the polymerization temperature can be about 30 to 100°C, and the polymerization time can be 0.5 to 20 hours.
[0072] In the polymerization process of the acrylic polymer, a polymerization initiator can be used together. The polymerization initiator is a medium that causes the polymerization reaction of each composition, and if the content is less than 0.1 parts by weight, unreacted monomers may remain in the composition, and if it exceeds 5.0 parts by weight, there is a risk of unreacted initiator remaining, which may reduce adhesive strength.
[0073] As the polymerization initiator, any compound capable of generating radicals can be used, and mainly peroxides or azo compounds can be used. Specifically, examples of the azo polymerization initiator include azobisisobutyronitrile, azonitrile, azoester, azoamide, azoamidine, azoimidazoline, or a mixture thereof. Examples of the peroxide polymerization initiator include benzoyl peroxide, acetyl peroxide, dilauryl peroxide, di-tert-butyl peroxide, cumyl hydroperoxide, hydrogen peroxide, or a mixture thereof. In addition to the above polymerization initiators, known acetal, hemiacetal, and redox polymerization initiators may be used. The polymerization initiator is not limited to the above examples, and various polymerization initiators not mentioned may be used in the preparation of the acrylic polymer.
[0074] The adhesive composition of the present application may contain additives in addition to the adhesive polymer, the acrylic polymer. The additives may be compounds used in adhesive formulations to increase the adhesion of the adhesive surface. The additives may generally be substances having a low molecular weight of 3,000 or less and a high glass transition temperature (Tg). The additives may increase the adhesive strength of the polymer at room temperature and act as a plasticizer for the polymer at high temperatures. As the content of the additives in the adhesive composition increases, the toughness and tackiness of the adhesive composition may increase and the viscosity may decrease. An increase in the content of the additives may result in a decrease in the thermal stability of the adhesive and a worsening of its color and odor, so that it may be necessary to consider the selection of the appropriate additives and the optimization of the content of the additives depending on the required quality.
[0075] As additives, for example, terpene-based or rosin-based additives can be mainly used, including polyterpenes, terpene phenolics, rosin esters, etc. Rosin esters have a very narrow molecular distribution and both lipophilic and hydrophilic structures, making them advantageous for use in a wide range of polymers.
[0076] Additives used in the adhesive composition can be selected taking into consideration the solubility parameter of the adhesive polymer. To facilitate dissolution and dispersion, additives having a solubility index similar to that of the adhesive polymer can be used in the preparation of the adhesive composition. Here, the solubility index is defined as the Hildebrand solubility parameter (HSP, unit: MPa). 0.5 ) can be used. This can be explained by the fact that the more similar the HSP values of two substances are, the more likely they are to dissolve, disperse, etc.
[0077] Specifically, the HSP value can be calculated using the following formula:
number
[0078] For example, the adhesive polymer of one embodiment polymerized with the above monomer components and composition ratio may have an HSP of 18 to 25, 20 to 25, or 21 to 23. Examples of additives that can be used at this time include terpene phenols or rosin esters having an HSP of 19 to 22. Polyterpenes, which are one of the additives mainly used in adhesives, have an HSP of 16, and may not be suitable for use with the adhesive polymer. When an additive with a large solubility index difference is applied to the adhesive polymer, it is not easy to disperse and dissolve with the adhesive polymer, and a haze phenomenon that appears blurred on the mixed solution may occur.
[0079] The adhesive composition may contain 30% to 70% by weight of the adhesive polymer and 30% to 70% by weight of the additive. The adhesive composition may contain 50% to 70% by weight of the adhesive polymer and 30% to 50% by weight of the additive. The ratio may be changed in consideration of the desired toughness, adhesion, viscosity, etc. In this case, the ratio may be based on the adhesive composition containing only the adhesive polymer and the additive, or, when the adhesive composition contains a solvent, etc., it may be based on the adhesive polymer and the additive only, excluding the solvent or other substances.
[0080] The adhesive strength of the adhesive composition can be further improved by adding an additive to the adhesive polymer, compared to when only the adhesive polymer is included. By including the additive, the adhesive strength of the adhesive composition can be improved to 25 gf / mm 2 Specifically, the adhesive strength of the adhesive composition may be 40 or more, 80 or more, 85 or more, or 90 or more, and may be 40 to 45, 80 to 95, or 85 to 92 gf / mm depending on the ratio of the additive. 2 may be also possible.
[0081] The viscosity of the adhesive composition is preferably 4000 cPs or less or 3500 cPs or less at 80°C, which may be to allow the adhesive composition to be discharged in a uniform size through the spraying device as described above. At this time, the diameter of the discharged adhesive composition may be 1 mm or less. In one example, the viscosity of the adhesive composition may have a value of 2200 to 2500 cPs or 2200 to 2400 cPs at 80°C.
[0082] The glass transition temperature of the adhesive composition varies depending on the ratio of the adhesive polymer and the additive. As the ratio of the additive increases, the glass transition temperature of the adhesive composition decreases. For example, when 100 parts by weight of the composition contains 50 parts by weight of the adhesive polymer and 50 parts by weight of the additive, the glass transition temperature of the adhesive composition may be -50 Tg (°C) or lower. In another example, when 100 parts by weight of the composition contains 30 parts by weight of the adhesive polymer and 70 parts by weight of the additive, the glass transition temperature may have a value of the -60 Tg (°C) level. Here, 100 parts by weight of the composition may contain only the additive and the adhesive polymer.
[0083] Meanwhile, when considering the long-term usability and safety of the adhesive composition, it is preferable that the adhesive composition does not undergo an oxidation reaction when a voltage is applied to the adhesive composition. Specifically, it is preferable that the adhesive composition does not undergo an oxidation reaction when a voltage of 4.0 V or more is applied to the adhesive composition.
[0084] Meanwhile, the adhesive composition of the present invention may be provided in a gel form and may be usable as an adhesive by itself. Therefore, the adhesive composition according to an embodiment of the present invention does not have to be provided in a form dissolved in a separate solvent or dispersed in a dispersion medium. The adhesive composition according to an embodiment of the present invention may be provided as the acrylic polymer and the additive by itself or as the acrylic polymer and the additive containing some additives.
[0085] In the following, preferred examples are presented to aid in understanding the present invention, but the following examples are merely illustrative of the present invention and are not intended to limit the scope of the present invention.
[0086] Hereinafter, a suitable acrylic polymer will be selected through examples and comparative examples of acrylic polymers, and examples and comparative examples of adhesive compositions containing the selected acrylic polymers and additives will be described.
[0087] 1. Production of acrylic polymer A monomer mixture was prepared by mixing methyl methacrylate (MMA), butyl acrylate (BA), 2-ethylhexyl acrylate (2-EHA) and / or 2-hydroxyethyl acrylate (2-HEA) in the monomer ratio (wt%) shown in the table below. Methyl methacrylate (MMA), butyl acrylate (BA), 2-ethylhexyl acrylate (2-EHA), and 2-hydroxyethyl acrylate (2-HEA) can be represented by the following chemical formulas 4 to 7, respectively. [Chemical formula 4] [ka] [Chemical formula 5] [ka] [Chemical formula 6] [ka] [Chemical formula 7] [ka]
[0088] The monomer mixture was mixed with 2 to 2.5 parts by weight of benzoyl peroxide, a polymerization initiator, based on 100 parts by weight of the monomer mixture, and a suspension was prepared by adding distilled water to a round-bottom flask to completely dissolve PVA (poly vinyl alcohol), a suspending agent. Here, PVA can be used at a level of 0.2 parts by weight based on 100 parts by weight of the monomer mixture. After creating polymerization conditions at 90°C using a heating mantle located at the bottom of the round-bottom flask, the monomer mixture containing the polymerization initiator was added to the round-bottom flask and stirred for more than 3 hours. After stirring, the acrylic polymer contained in the mixed solution was filtered through filter paper, washed, and then dried in a vacuum oven for more than one day.
[0089] The acrylic polymers prepared by the above-mentioned preparation method are as follows. The molecular weight, viscosity, adhesive strength, and dispenser jetting stability of the acrylic polymers were evaluated. The specific evaluation methods for adhesive strength and dispenser jetting stability will be described later.
[0090] [Table 1] [Table 1]
[0091] Referring to Table 1 above, the acrylic polymer according to Preparation Example 1 has a molecular weight of 90,000 to 150,000, specifically, a value of 120,000 to 140,000, and a viscosity of 3,000 cPs or less at 80°C.
[0092] Comparative Preparation Example 1 exhibits almost the same physical properties as Preparation Example 1, except for adhesive strength. However, the adhesive strength of Comparative Preparation Example 1 is half that of Preparation Example 1, and it was confirmed that the performance as an adhesive composition is somewhat inferior. This may be due to the somewhat lower ratio of monomers containing hydroxyl groups.
[0093] It can be seen that the content of 2-HEA, a monomer containing a hydroxyl group, is somewhat higher at 40% or more in Comparative Preparation Example 2 and Comparative Preparation Example 3 than in Preparation Example 1, which increases the viscosity and thus reduces the dispenser jetting stability to some extent. Also, since Comparative Preparation Examples 2 and 3 contain a higher ratio of 2-EHA than MMA, the increase in viscosity and the resulting decrease in dispenser jetting stability may be due to the content of 2-EHA.
[0094] In Comparative Preparation Example 4, the content of 2-HEA, a monomer containing a hydroxyl group, was 10%, which was somewhat lower than that in Preparation Example 1, and it was confirmed that the adhesive strength was significantly reduced.
[0095] In Comparative Preparation Example 5, the content of 2-HEA, a monomer containing a hydroxyl group, is 60%, which is somewhat higher than that in Preparation Example 1. This resulted in an increase in viscosity and a somewhat lower dispenser jetting stability.
[0096] The acrylic polymer of Production Example 1-1 has a molecular weight of 80,000 to 140,000, specifically, a value of 110,000 to 130,000, and has a viscosity of 3,000 cPs or less at 80°C.
[0097] The acrylic polymer of Production Example 1-2 has a molecular weight of 100,000 to 160,000, specifically, a value of 120,000 to 140,000, and has a viscosity of 3,000 cPs or less at 80°C.
[0098] In the case of Preparation Example 1-1, the adhesive strength is slightly reduced compared to Preparation Example 1, but in the case of Preparation Example 1-2, the adhesive strength can be improved by reducing the amount of MMA and increasing the amount of BA (butyl acrylate) compared to Preparation Example 1-1.
[0099] Comparative Preparation Example 1-1 shows almost the same physical properties as Preparation Example 1-1 except for adhesive strength. However, the adhesive strength of this comparative example is less than half that of Preparation Example 1-1, and it was confirmed that the performance as an adhesive composition is inferior. This may be due to the somewhat low ratio of monomers containing hydroxyl groups.
[0100] It can be seen that the content of 2-HEA, a monomer containing a hydroxyl group, in Comparative Preparation Example 1-2 is 20%, which is somewhat lower than that in Preparation Example 1-1, and the adhesive strength was significantly reduced.
[0101] With reference to these measurement results, it is determined that the properties of Preparation Examples 1, 1-1, and 1-2, which have relatively excellent dispenser jetting stability and adhesive strength, are more suitable for use in adhesive compositions than the other Examples and Comparative Examples. This may be because if the ratio of the monomer containing a hydroxyl group is 40% or more, the viscosity increases significantly, resulting in a somewhat poor dispenser jetting stability, and if it is 20% or less, the basic adhesive strength required for an adhesive composition is significantly reduced.
[0102] With reference to the ratio between the monomers shown in Table 1, it may be appropriate for the acrylic polymer to contain more than 20 parts by weight and less than 40 parts by weight of the hydroxyalkyl (meth)acrylate monomer relative to 100 parts by weight of the monomer mixture. It may be preferable for the acrylic polymer to contain 60.1 to 79.9 parts by weight of the alkyl (meth)acrylate monomer and 20.1 to 39.9 parts by weight of the hydroxyalkyl (meth)acrylate monomer relative to 100 parts by weight of the monomer mixture.
[0103] In a preferred embodiment, the weight average molecular weight of the acrylic polymer may be 120000 to 140000. In a preferred embodiment, the viscosity of the acrylic polymer may be 2750 cPs to 3500 cPs or 2800 cPs to 3000 cPs at 80° C., and the adhesive strength of the acrylic polymer may be 20 gf / mm 2 or more than 25gf / mm 2 or more than 27gf / mm 2 It may be more than that.
[0104] 2. Preparation of adhesive composition containing additives Example 1 Acrylic polymer production In this example, the acrylic polymer of Preparation Example 1 among the acrylic polymers evaluated in '1. Preparation of acrylic polymer' was used.
[0105] Additive preparation The additive in this embodiment is a rosin ester-based material, SYLVALITE sold by KRATON. TM RE 10L was used. TM RE 10L is referred to as the first additive.
[0106] Preparation of the adhesive composition The obtained acrylic polymer and the first additive were added to prepare an adhesive composition. Here, the acrylic polymer and the first additive were mixed in a ratio of 30 wt % and 70 wt %, respectively, excluding other additives.
[0107] Example 2 This example was prepared in the same manner as in Example 1, except that the acrylic polymer and the first additive were mixed in a ratio of 50% by weight each during preparation of the adhesive composition.
[0108] Example 3 This example was prepared in the same manner as in Example 1, except that the acrylic polymer and the first additive were mixed in a ratio of 70% by weight and 30% by weight, respectively, during the preparation of the adhesive composition.
[0109] Example 4 This example was prepared in the same manner as in Example 1, except that a fourth additive was used instead of the first additive, and the acrylic polymer and the fourth additive were mixed in a ratio of 30% by weight and 70% by weight, respectively. The fourth additive was a rosin ester-based material, SYLVALITE® sold by KRATON. TM RE 25 was used. TM RE 25 is referred to as the fourth additive.
[0110] Example 5 This example was prepared in the same manner as in Example 4, except that the acrylic polymer and the fourth additive were mixed in a ratio of 50% by weight and 50% by weight, respectively, during the preparation of the adhesive composition.
[0111] Example 6 This example was prepared in the same manner as in Example 4, except that the acrylic polymer and the fourth additive were mixed in a ratio of 70 wt % and 30 wt %, respectively, during the preparation of the adhesive composition.
[0112] Comparative Example 1 This comparative example was prepared in the same manner as in Example 1, except that the second additive was used instead of the first additive, and the acrylic polymer and the second additive were mixed in a ratio of 50% by weight. Here, the second additive was a terpene phenol-based additive, SYLVARES® sold by KRATON. TM TP 300.
[0113] Comparative Example 2 This comparative example is the same as Example 1, except that a third additive was used instead of the first additive, and the acrylic polymer and the third additive were mixed in a ratio of 50% by weight each. Here, the third additive was a polyterpene additive, SYLVARES® sold by KRATON. TM TR M1115.
[0114] Comparative Example 3 This comparative example can be explained in the same manner as Example 1, except that the acrylic polymer and the first additive were mixed in ratios of 75% by weight and 25% by weight, respectively, during the preparation of the adhesive composition.
[0115] Comparative Example 4 This comparative example can be explained in the same manner as Example 1, except that the acrylic polymer and the first additive were mixed in ratios of 20 wt % and 80 wt %, respectively, during the preparation of the adhesive composition.
[0116] Comparative Example 5 This comparative example can be explained in the same manner as Example 1, except that the acrylic polymer and the first additive were mixed in ratios of 25% by weight and 75% by weight, respectively, during the preparation of the adhesive composition.
[0117] Comparative Example 6 This comparative example can be explained in the same manner as Example 1, except that the acrylic polymer and the first additive were mixed in a ratio of 80% by weight and 20% by weight, respectively, during the preparation of the adhesive composition.
[0118] Comparative Example 7 This comparative example can be explained in the same manner as Example 4, except that the acrylic polymer and the fifth additive were mixed in ratios of 20 wt % and 80 wt %, respectively, during the preparation of the adhesive composition.
[0119] Comparative Example 8 This comparative example can be explained in the same manner as Example 4, except that the acrylic polymer and the fourth additive were mixed in ratios of 25% by weight and 75% by weight, respectively, during the preparation of the adhesive composition.
[0120] Comparative Example 9 This comparative example was prepared in the same manner as in Example 4, except that the acrylic polymer and the fourth additive were mixed in ratios of 75% by weight and 25% by weight, respectively, during the preparation of the adhesive composition.
[0121] Comparative Example 10 This comparative example can be explained in the same manner as Example 4, except that the acrylic polymer and the fourth additive were mixed in a ratio of 80 wt % and 20 wt %, respectively, during the preparation of the adhesive composition.
[0122] Evaluation of adhesive compositions Table 2 below is a table in which the adhesive compositions of Examples 1 to 6 and Comparative Examples 1 to 10 are evaluated for viscosity, glass transition temperature, dispenser jetting stability, adhesive strength, and the like.
[0123] The molecular weight of the adhesive composition can be measured by a conventional method known in the art. The molecular weights in the present examples and comparative examples are weight average molecular weights measured by GPC (Gel Permeation Chromatograph) and converted to standard polystyrene, and the values in the examples were in the range of 70,000 to 85,000 (PDI>2.5).
[0124] The viscosity of the adhesive composition can be measured by a conventional method known in the art. Conventional viscosity measurements can be performed using a capillary viscometer, a rotational viscometer, a falling ball viscometer, a pressure driven method, or other devices and methods. The viscosity of the present embodiment and comparative examples was measured using an Anton Paar MCR-302 Rheometer (Cone plate: 25mmφ∠=2°, 1Hz, d=0.105mm), and the value was 4000cPs or less, or 3500cPs or less, or 2200cPs to 2500cPs, or 2200cPs to 2400cPs at 80°C.
[0125] The glass transition temperature of the adhesive composition can be measured by a conventional method known in the art. For example, the glass transition temperature can be measured by DSC (Differential Scanning Calorimetry).
[0126] The adhesive strength of the adhesive composition can be measured by a conventional method known in the art. For example, as shown in Fig. 2, 15 dots of adhesive composition 320 are applied between two adherends 310 at intervals of 3 mm, and then the adherends 310 coated with adhesive composition 320 are placed between two tension jigs, and the tension jigs are moved in a direction perpendicular to one surface of the adherends 310 to measure the adhesive strength.
[0127] Dispenser jetting stability was evaluated by comparing the diameter of dots after continuous jetting for 30 minutes using a Nordson dispenser. Specifically, the diameter of a dot dispensed at a first point in time was compared with the diameter of a dot dispensed at a second point in time, 30 minutes after the first point in time. If the deviation in dot diameter was less than 5%, the jetting stability was evaluated as being satisfactory (OK). The experiment was performed using a Vulcan dispenser with a piezo drive system, and the dispenser temperature was 120℃ during dispensing.
[0128] [Table 2] [Table 2]
[0129] The adhesive polymer contained in Examples 1 to 6 and Comparative Examples 1 to 10 is the one according to the above-mentioned Production Example 1, and may have a solubility index of HSP of 18 to 25 or 20 to 25, preferably 21 to 23. Here, the first additive and / or the fourth additive used in Examples 1 to 6 may be a rosin ester-based substance, and may have a solubility index of HSP of 19 to 22. In addition, the adhesive polymer contained in Examples 1 to 6 and Comparative Examples 2 to 8 may have a glass transition temperature of -100 to -90°C, or close to -95°C.
[0130] The first additive used in Examples 1-3 and the fourth additive used in Examples 4-6 may have a glass transition temperature value of 0° C. or less. The first additive may have a glass transition temperature value of -25° C. or less, -35° C. or more, or close to -30° C., and the fourth additive may have a glass transition temperature value of -13° C. The glass transition temperature values of the second and third additives used in Comparative Examples 1 and 2 may be higher than the glass transition temperature values of the first and fourth additives.
[0131] In Examples 1 to 6, a first additive having a solubility index similar to that of the adhesive polymer of Preparation Example 1 was used, and it was shown that as the ratio of the first additive increased, the viscosity and glass transition temperature of the adhesive composition decreased and the adhesive strength improved. Specifically, the adhesive compositions according to Examples 1 to 6 had a viscosity of 2200 cPs to 2500 cPs at 80°C and a glass transition temperature of -40 Tg (°C) or less.
[0132] The adhesive strength of ordinary adhesive polymers (27-30gf / mm 2), the adhesive compositions of Examples 1 to 6 have a higher adhesive strength, which suggests that the adhesive polymer and the first additive or the adhesive polymer and the fourth additive are well mixed together. Here, Examples 2 and 3 do not show a large difference in viscosity, but show a difference of almost twice as much in adhesive strength, so that Example 2 or Example 1 may be more preferable than Example 3 for use as an adhesive. Specifically, the adhesive compositions of Examples 2 and 3 have a viscosity of 2300 to 2500 cPs at 80°C and a glass transition temperature of -55Tg(°C) or less.
[0133] When comparing Example 2 containing the same ratio of adhesive polymer with Comparative Examples 1 and 2, it was confirmed that the viscosity and glass transition temperature increased significantly and the adhesive strength decreased slightly depending on the type of additive.
[0134] On the other hand, in the case of Comparative Example 1 in which a terpene phenol-based second additive was used, the adhesive strength of Comparative Example 1 was lower than that of the adhesive polymer and Example 2, and the viscosity and glass transition temperature were higher. This may be due to the poor adhesive properties of the material itself, as estimated from the glass transition temperature of the second additive. In addition, this may be due to the large difference between the solubility index of the terpene phenol-based second additive and that of the adhesive polymer, which may cause the adhesive polymer and the additive to not mix well with each other.
[0135] In the case of Comparative Example 2, a polyterpene-based third additive having an HSP of 16 was used. Haze was observed with the naked eye, and no separate adhesive strength was measured. However, considering that the dispersibility with the adhesive polymer was very low, it is expected to have similar or even lower adhesive strength than Comparative Example 1.
[0136] With reference to the ratio between the additives and the copolymer shown in Table 2, it may be preferable that the copolymer is included in an amount of 30 to 70 parts by weight and the additive is included in an amount of 30 to 70 parts by weight, relative to 100 parts by weight of the adhesive composition. It may also be preferable that the copolymer is included in an amount of 30 to 50 parts by weight and the additive is included in an amount of 50 to 70 parts by weight, relative to 100 parts by weight of the adhesive composition. In this case, 100 parts by weight of the adhesive composition may include only the copolymer and the additive. That is, the total amount of the additive and the copolymer may be 100 parts by weight.
[0137] In the case of Comparative Examples 3 and 6, the adhesive strength was significantly reduced compared to Examples 1 to 3, and in the case of Comparative Examples 4 and 5, the adhesive accumulated at the end of the dispenser after a certain period of time, causing deviation in the dot size of the adhesive, resulting in problems with dispenser jetting stability.
[0138] In the case of Comparative Examples 7 and 8, the adhesive strength is slightly decreased compared to Examples 4 and 5, but the adhesive accumulates at the end of the dispenser after a certain period of time, causing deviation in the dot size of the adhesive, resulting in problems with dispenser jetting stability.
[0139] In the cases of Comparative Examples 9 and 10, the adhesive strength is significantly reduced as compared to Examples 4-5.
[0140] In a preferred embodiment, the adhesive composition has a glass transition temperature (Tg(℃)) of −40 or less or −50 or less. In a preferred embodiment, the adhesive composition has a viscosity of 2200cPs to 2500cPs or 2200cPs to 2400cPs at 80℃. In a preferred embodiment, the adhesive composition has an adhesive strength of 40gf / mm 2 Above, 85gf / mm 2 or more, or 85~92gf / mm 2 It may be more than that.
[0141] Meanwhile, FIG. 3 is a graph showing the LSV (Linear Sweep Voltammetry) of an adhesive composition according to one embodiment of the present invention.
[0142] 3, the adhesive composition including the first additive did not show an oxidation reaction even above 4.0 V, but the adhesive compositions including the second and third additives showed an oxidation reaction above 4.0 V, specifically between 4.0 V and 4.5 V. Inferred from this, the chemical stability of the rosin ester-based additive may be superior to that of the terpene phenol-based or polyterpene-based additives.
[0143] In order to aid in the understanding of the present invention, preferred examples of the use of the adhesive composition are presented below. However, the following examples are merely illustrative of the present invention, and the scope of the present invention is not limited to the following examples.
[0144] FIG. 4 is a diagram illustrating an example in which an adhesive composition according to an embodiment of the present invention is used in a process for manufacturing an electrode assembly, and FIG. 5 is a diagram illustrating another example in which the adhesive composition according to an embodiment of the present invention is used in a process for manufacturing an electrode assembly.
[0145] 4 and 5, the adhesive composition of the present embodiment can be provided to fix a separator or electrodes in a process for manufacturing an electrode assembly. The adhesive composition of the present embodiment can be provided to a separator before a negative electrode and a positive electrode are inserted. The adhesive composition of the present embodiment can be used as it is, or can be provided as a so-called adhesive by additionally containing other materials.
[0146] Specifically, in the process of manufacturing the electrode assembly, the separators 30a, 30b are provided from at least two places and can be continuously inserted, and the positive electrode 10 or the negative electrode 20 is inserted thereto, thereby manufacturing a unit cell 40 having the order of positive electrode 10 / upper separator 30b / negative electrode 20 / lower separator 30a or negative electrode 20 / upper separator 30b / positive electrode 10 / lower separator 30a. The positive electrode 10 or the negative electrode 20 is cut by the respective cutters 60a, 60b before being stacked on the separators 30a, 30b. 60The cutter can be cut to a predetermined size through the cutting tool.
[0147] In this case, the adhesive composition can be applied to the positions where the electrodes (positive electrode 10, negative electrode 20) are directly attached to the separators 30a, 30b or to the positions where the separators 30a, 30b are attached to each other, thereby preventing the electrodes (positive electrode 10, negative electrode 20) from moving out of their fixed positions.
[0148] The adhesive composition can be applied through a jetting device 70, and the method is not limited thereto, but it can be applied by, for example, spray jetting, ink jet jetting, or the like.
[0149] Here, the spray direction of the adhesive composition may be different depending on the positions of the separators 30a and 30b as shown in Fig. 4, or may be provided vertically (from top to bottom) to minimize the influence of gravity as shown in Fig. 5. Here, the spray direction may be fixed as shown in Fig. 5, but this is not necessarily the case, and the spray direction may be adjusted depending on the usage environment.
[0150] In the case of the configuration shown in FIG. 5, the spraying device 70 may include a first nozzle 70a, a second nozzle 70b, and a third nozzle 70c for spraying adhesive onto one side of the separators 30a and 30b. Here, the first nozzle 70a may spray adhesive onto the lower separator 30a, and the second nozzle 70b and the third nozzle 70c may spray adhesive onto two sides of the upper separator 30b, respectively. At this time, the separators 30a and 30b may change their traveling direction via the guide roller 51. More specifically, the first nozzle 70a may spray adhesive onto the lower separator 30a before the negative electrode 20 is provided onto the lower separator 30a, the second nozzle 70b may spray adhesive onto the upper separator 30b after the negative electrode 20 is provided onto the lower separator 30a, and the third nozzle 70c may spray adhesive onto the upper separator 30b before the positive electrode 10 is provided onto the upper separator 30b.
[0151] Here, each nozzle 70a, 70b, 70c may include a plurality of nipples (α, β, γ) spaced apart from one another, and the spray speed, spray amount, spray area, etc. of each of these may be individually adjusted, so that the adhesive may be applied at narrow or wide intervals as required.
[0152] 5, the electrodes (positive electrode 10, negative electrode 20) are stored in a pre-cut state and can be moved to the separators 30a, 30b by the first gripper 100a and the second gripper 100b. At this time, the electrodes (positive electrode 10, negative electrode 20) can be moved by the tables 110a, 110b.
[0153] After the adhesive is applied, the laminated separators 30a, 30b and electrodes (positive electrode 10, negative electrode 20) can pass between nip rollers 50a, 50b, and the bonding strength between the separators 30a, 30b and the electrodes (positive electrode 10, negative electrode 20) can be improved through the nip rollers 50a, 50b. At this time, the pressure or temperature applied by the nip rollers 50a, 50b may be lower than the pressure or temperature applied in the conventional method.
[0154] As described above, when the adhesive composition of the present invention is used in the electrode assembly manufacturing process, heat and pressure are not applied or weaker heat and pressure than before are applied when lamination is performed between the electrodes (positive electrode 10, negative electrode 20) and the separators 30a, 30b. This prevents misalignment between the separators 30a, 30b and the electrodes (positive electrode 10, negative electrode 20) during the manufacturing process and prevents damage and deformation of the separators 30a, 30b and the electrodes (positive electrode 10, negative electrode 20).
[0155] The above describes a number of cases where the adhesive composition is used in an electrode assembly among various examples of applications in which the adhesive composition can be used, and Fig. 4 and Fig. 5 are merely intended to aid in understanding the manufacturing process of an electrode assembly in which the adhesive composition can be used, and the examples of use of the adhesive composition should not be limited by the above description. Therefore, it is obvious that the adhesive composition according to an embodiment of the present invention can be used in various ways other than the above examples, and the adhesive composition according to the present embodiment can be widely used not only in the manufacturing process of an electrode assembly but also in other industrial fields.
[0156] Hereinafter, a unit cell including an adhesive composition according to an embodiment of the present specification will be described. The unit cell described below may be formed through the manufacturing process of the electrode assembly described above, but it should be noted that this is not necessarily the case and may be formed in a manner different from the above-mentioned use example.
[0157] FIG. 6 illustrates a unit cell including an adhesive composition according to one embodiment of the present invention.
[0158] Referring to FIG. 6, the unit cell of the present embodiment may be manufactured by stacking a lower separator 30a, one of the negative or positive electrodes (positive electrode 10, negative electrode 20), an upper separator 30b, and the other of the negative or positive electrodes (positive electrode 10, negative electrode 20) in this order from bottom to top. Here, an adhesive a may be applied to at least one surface of the electrodes (positive electrode 10, negative electrode 20) and the separators 30a, 30b, thereby fixing the electrodes (positive electrode 10, negative electrode 20) and the separators 30a, 30b to each other. Here, FIG. 6 shows a structure in which the lower separator 30a, the negative electrode 20, the upper separator 30b, and the positive electrode 10 are stacked from bottom to top, but this is not necessarily the case, and the lower separator 30a, the positive electrode 10, the upper separator 30b, and the negative electrode 20 may be stacked in this order. Here, the adhesive a may include the above-mentioned adhesive composition.
[0159] The adhesive a may be for bonding the separators 30a, 30b. The adhesive a may be applied to one side of the upper separator 30b or the lower separator 30a to bond the upper separator 30b and the lower separator 30a. By bonding the upper separator 30b and the lower separator 30a, the movement of the electrodes (positive electrode 10, negative electrode 20) located therebetween is restricted, and the positions of the electrodes (positive electrode 10, negative electrode 20) can be fixed. In this case, the adhesive a may be applied to an area of the upper separator 30b or one side of the lower separator 30a where the electrodes (positive electrode 10, negative electrode 20) are not stacked.
[0160] The adhesive a may be for bonding between the separators 30a, 30b and the electrodes (positive electrode 10, negative electrode 20). The adhesive a may be applied to one side of the separators 30a, 30b or the electrodes (positive electrode 10, negative electrode 20) to bond the separators 30a, 30b and the electrodes (positive electrode 10, negative electrode 20) facing each other. For example, the adhesive a may be provided between the lower separator 30a and the negative electrode 20 to fix the lower separator 30a and the negative electrode 20. The adhesive a may be provided between the upper separator 30b and the positive electrode 10 to fix the upper separator 30b and the positive electrode 10. In this case, the adhesive a may be applied to the electrodes (positive electrode 10, negative electrode 20) or may be applied to the upper separator 30b or to one side of the lower separator 30a in a region where the electrodes (positive electrode 10, negative electrode 20) are stacked.
[0161] Meanwhile, the adhesive a applied on the electrodes (cathode 10, anode 20) and the separators 30a, 30b may be applied in a plurality of rows from a plurality of points spaced apart from one another along a specific direction. For example, as shown in Figures 4 and 5, the sprayer 70 may include a plurality of nipples (α, β, γ) spaced apart from one another, and each of these may spray adhesive a continuously, thereby forming a plurality of rows of applied adhesive a.
[0162] Here, the adhesive a in a particular row may be applied at narrower or wider intervals than the adhesive a in other rows. Also, the area of adhesive a applied in a particular row may be larger than the area of adhesive a applied in other rows. For example, the adhesive may be applied at narrower intervals to the contact point between the negative electrode tab 20a and the positive electrode tab 10a, where a stronger adhesive strength is required. This may be achieved by adjusting the injection speed, injection amount, injection area, etc. between the nipples (α, β, γ) included in the injection device 70 of FIG. 5.
[0163] 7 is a diagram illustrating an example of an area where an adhesive is applied in a unit cell including an adhesive composition according to an embodiment of the present invention. The dotted areas in FIG. 7 may indicate the positions where the adhesive is applied.
[0164] 7, the electrodes (positive electrode 10, negative electrode 20) may have a rectangular shape having two relatively short short sides and two relatively longer long sides. When the electrodes (positive electrode 10, negative electrode 20) are stacked on the separators 30a, 30b, the electrodes (positive electrode 10, negative electrode 20) may be arranged such that their long sides are parallel to the width direction of the separator.
[0165] 7(a), the adhesive may be provided on the contact surfaces of two separators 30a, 30b facing each other. The adhesive may be provided on the periphery of the separators 30a, 30b where the electrodes (cathode 10, anode 20) are not stacked. The adhesive may be used to bond the separators 30a, 30b together, thereby restricting the movement of the electrodes (cathode 10, anode 20) located between the two separators 30a, 30b.
[0166] The adhesive may be provided on the contact surfaces of the electrodes (positive electrode 10, negative electrode 20) and the separators 30a, 30b as shown in Fig. 7(b). By providing the adhesive on the contact surfaces of the electrodes (positive electrode 10, negative electrode 20) and the separators 30a, 30b, the relative movement between the electrodes (positive electrode 10, negative electrode 20) and the separators 30a, 30b can be restricted. For example, the adhesive may be provided at positions where both short sides of the electrodes (positive electrode 10, negative electrode 20) are located so that the electrodes (positive electrode 10, negative electrode 20) and the separators 30a, 30b are bonded only to the short sides of the electrodes (positive electrode 10, negative electrode 20).
[0167] The adhesive may be provided not only on the surface where the electrodes (positive electrode 10, negative electrode 20) and the separators 30a, 30b contact each other as shown in FIG. 7(c), but also on all surfaces where the separators 30a, 30b contact each other. The adhesive may be provided at positions corresponding to the four vertices of the electrodes (positive electrode 10, negative electrode 20) as shown in FIG. 7(d) and FIG. 7(e), or may be provided at the regions where the short and long sides of the electrodes (positive electrode 10, negative electrode 20) correspond and the central region as shown in FIG. 7(f). The application positions of the adhesive shown in FIG. 7 are merely examples, and the positions where the adhesive or adhesive composition is provided may be various other than those shown in the above drawings, so the application positions should not be limited by the drawing of FIG. 7.
[0168] 8 to 10 are diagrams showing the electrodes or separators of FIG. 6 coated with adhesive.
[0169] 8 is a diagram showing a coating pattern of adhesive a provided between the lower separator 30a and the negative electrode 20. The form shown in FIG. 8 may be a coating pattern of adhesive a sprayed onto the lower separator 30a before the negative electrode 20 is laminated onto the lower separator 30a. Here, adhesive a may be formed more densely at the portion where the negative electrode tab 20a is located based on both short sides of the negative electrode 20. For example, adhesive a may be formed by not applying adhesive a to the middle nipple β of the nipples (α, β, γ) and increasing the spray speed of the nipple α located close to the negative electrode tab 20a among the nipples α and γ at both ends.
[0170] Fig. 9 is a diagram showing an adhesive application pattern provided between the negative electrode 20 and the upper separator 30b, and Fig. 10 is a diagram showing an adhesive application pattern provided between the upper separator 30b and the positive electrode 10. The form as shown in Fig. 9 is an application pattern of adhesive a sprayed onto the upper separator 30b after the upper separator 30b is laminated on the negative electrode 20, and the form as shown in Fig. 10 may be an application pattern of adhesive a sprayed onto the upper separator 30b before the upper separator 30b is laminated on the positive electrode 10. As in Fig. 8, the adhesive a in Figs. 9 and 10 may be applied more densely at the position where the positive electrode tab 10a is located.
[0171] A battery cell including the above-mentioned unit cell will be described below.
[0172] Meanwhile, the unit cells may be sealed inside a cell case to provide a battery cell. Specifically, the battery cell may include an electrode assembly including at least one unit cell, an electrode tap extending from one end of an electrode included in the electrode assembly, an electrode lead coupled to the electrode tap, and a cell case accommodating the electrode assembly with one end of the electrode lead extended to the outside.
[0173] The electrode assembly may include at least one unit cell. The electrode assembly may be formed by stacking at least two unit cells. The unit cell may be a power generating element capable of being charged and discharged. The unit cell may include an electrode and a separator, and the electrode may be provided as a positive electrode or a negative electrode. A separator is interposed between each electrode, and the unit cell may have a structure in which a separator / anode / separator / positive electrode are alternately stacked. For more detailed information regarding the unit cell, please refer to the above content.
[0174] An electrode tab may be a portion that extends from a plurality of electrodes and is not coated with an electrode active material. An electrode tab connected to a positive electrode may be called a positive electrode tab, and an electrode tab connected to a negative electrode may be called a negative electrode tab. An electrode tab may extend in one direction or in both directions from an end of a positive electrode or a negative electrode of a unit cell.
[0175] The electrode lead may electrically connect the unit cell in the cell casing to an external member outside the cell casing. One end of the electrode lead may be drawn out to the outside of the cell casing, and the other end of the electrode lead may be connected to an electrode tap inside the cell casing. The connection between the electrode lead and the electrode tap may be formed by welding.
[0176] The cell case may be used to seal the unit cells located therein by sealing the periphery by heat fusion or the like. The cell case may generally be formed as a laminate structure of a resin layer / metal thin film layer / resin layer. In addition, the cell case may include an adhesive member such as a pressure-sensitive adhesive such as double-sided tape provided on the outer surface of the cell case or a chemical adhesive that bonds by a chemical reaction when bonded, in order to stably maintain the laminate structure when the battery cell stack is formed.
[0177] Fig. 11 is a graph showing the capacity measured in a battery cell according to an embodiment of the present invention, Fig. 12 is a graph showing the resistance measured in a battery cell according to an embodiment of the present invention, and Fig. 13 is a graph showing the capacity retention measured in a battery cell according to an embodiment of the present invention.
[0178] 11 and 12, it can be seen that the capacity and resistance of the unit cell are at the same level when the adhesive is used at 0.02 wt% and 1 wt% relative to the electrolyte according to the present embodiment, compared to the reference example (Ref) in which heat and pressure are applied to the electrodes and separator using a lamination method to assemble the unit cell without using an adhesive. Also, referring to FIG 13, it can be seen that the capacity retention rate of the unit cell is also at the same level as the existing method through a charge / discharge test.
[0179] The separator according to the embodiment described herein may be a CCS (Ceramic Coated Separator). In general, a separator includes an original film and a coating layer formed on at least one surface of the original film, and the coating layer may include alumina powder and a binder that binds them together. A safety reinforced separator (SRS) has a large amount of binder coated on the surface of the coating layer, but a CCS may not have a binder coated on the surface of the coating layer or may have a much lower binder content distributed on the surface compared to an SRS. For example, in the case of a CCS separator according to the present embodiment, the binder content coated on the surface of the coating layer of the separator may be about 3 wt% or less.
[0180] When the separator is CCS, the internal electrodes included in the electrode assembly are transported in an unfixed state, and so the alignment may become distorted during transport. Of course, when the separator is CCS, it can be fixed by heat and pressure, but the alignment of the internal electrodes may become distorted during the process of transporting the laminate of the electrodes and separator to a fixing device using heat and pressure after the laminate is formed. In addition, there is a disadvantage that an expensive separator with a high binder content must be used to attach the electrodes and separator using heat and pressure. In contrast, according to the present embodiment, the alignment of the internal electrodes can be prevented from becoming distorted during transport while increasing the fixing force.
[0181] FIG. 14 is a cross-sectional view showing an electrode assembly according to another embodiment of the present invention.
[0182] 14, the electrode assembly 3000 according to the present embodiment may include an electrode stack 42 manufactured by repeatedly forming a plurality of radical units 32. Here, the radical units 32 have a zigzag shape due to the folding of the separator 322, and the electrode stack 42 may include a plurality of radical units 32. 3112、3122 Cover the electrodes 3112、3122 In other words, the basic unit 32 may be a unit in which one side and the other side of the separator 322 are folded in sequence to form an electrode. 3112、3122Cover the electrode 3112、3122 and a separation membrane 322 may be laminated in this order.
[0183] The electrode assembly 3000 may have a fixing tape attached thereto, but instead of the fixing tape, one end of the separator 322 may surround a portion of the outer surface of the electrode stack 42. The basic unit 32 of this embodiment may be in a state in which the electrodes 3112, 3122 and the separator 322 are bonded to each other with an adhesive 34. The portion where the electrodes 3112, 3122 and the separator 322 are bonded to each other with the adhesive 34 may be a first bonding portion. Thus, the electrodes 3112, 3122 and the separator 322 can maintain their alignment due to the adhesive force of the adhesive 34.
[0184] In the electrode stack 42 of the present embodiment, the separator 322 covers the upper, lower and one side of the electrodes 3112 and 3122, and the stacked alignment state of the radical units 32 can be maintained without the fixing tape. In addition, when the fixing tape is attached to the outside of the electrode stack 42 of the present embodiment or when one end of the separator 322 is surrounded, the stacked alignment state of the radical units 32 can be more stably maintained.
[0185] In addition, in the electrode assembly 3000 manufactured in this embodiment, the adhesive 34 may be disposed at the same position between the electrodes 3112, 3122 and the separator 322. For example, as shown in Fig. 14, in the electrode assembly 3000 of this embodiment, the adhesive 34 disposed between the lower part of the first electrode 3112 and the separator 322 and the adhesive 34 disposed between the upper part of the first electrode 3112 and the separator 322 may be disposed on the same vertical line based on the bottom surface of the first electrode 3112 or the separator 322, respectively, and the intervals at which the adhesives 34 are disposed may be the same. This can be similarly explained in the case of the adhesive 34 disposed between the second electrode 3122 and the separator 322.
[0186] Accordingly, in the electrode assembly 3000 manufactured in this embodiment, the adhesive 34 is disposed at the same position between each of the electrodes 3112, 3122 and the separator 322, which is advantageous in that process time and efficiency can be increased.
[0187] FIG. 15 is a cross-sectional view showing an electrode assembly according to still another embodiment of the present invention.
[0188] 15, in the electrode assembly 4000 according to the present embodiment, the adhesive 34 is disposed between the electrodes 3112, 3122 and the separator 322, and the adhesives 34 disposed in adjacent layers may be disposed in an alternating manner. For example, as shown in FIG. 15, in the electrode assembly 4000 according to the present embodiment, The upper part of the second electrode 3122 and a first adhesive 34-1 located between the separation film 322. The lower part of the second electrode 3122 The second adhesive 34-2 located between the first adhesive 34-1 and the separation film 322 may be arranged alternately. In this case, the first adhesive 34-1 and the second adhesive 34-2 are merely arranged alternately, and the intervals at which they are applied may be the same. This is because 1st electrode 3112 and an adhesive positioned between the separator 322. 34 The same can be explained in the case of
[0189] However, the present invention is not limited thereto, and the structure in which the first adhesive 34-1 and the second adhesive 34-2 are alternately arranged can be manufactured by applying them in various ways.
[0190] As a result, in the electrode assembly 4000 of the present embodiment, the adhesive 34 is disposed between each of the electrodes 3112, 3122 and the separator 322, and the adhesives 34 disposed in adjacent layers are arranged in an alternating manner, thereby minimizing an increase in the thickness of the electrode assembly 4000 due to the adhesive 34. In addition, since the adhesives 34 disposed in adjacent layers are arranged in an alternating manner, the adhesives 34 can be more easily dissolved in the electrolyte contained in the battery cell.
[0191] Although the preferred embodiments of the present invention have been described in detail above, the scope of the present invention is not limited thereto, and various modifications and improvements made by those skilled in the art using the basic concept of the present invention defined in the following claims also fall within the scope of the present invention.
Claims
1. In a unit cell in which separation membranes and electrodes are stacked alternately, The unit cell is formed by stacking a lower separator, a first electrode, an upper separator, and a second electrode in this order, an adhesive is applied to one surface of at least one of the electrode and the separator, so that the electrode and the separator or the lower separator and the upper separator are bonded to each other; The adhesive comprises an adhesive composition including a copolymer and a rosin ester-based additive, The copolymer comprises 60.1 to 79.9% by weight of two or more alkyl (meth)acrylate repeating units (A) and 20.1 to 39.9% by weight of (meth)acrylate repeating units having a terminal hydroxyl group (B); The adhesive composition comprises 30% to 70% by weight of the copolymer and 30% to 70% by weight of the additive, unit cell.
2. The unit cell of claim 1 , wherein the adhesive is applied to one surface of the upper isolation film or the lower isolation film to adhere the upper isolation film and the lower isolation film.
3. The unit cell of claim 1 , wherein the adhesive is applied to one surface of the separator or the electrode to bond the separator and the electrode facing each other.
4. The alkyl (meth)acrylate repeating unit (A) is represented by the following formula 1: The unit cell according to claim 1 , wherein the (meth)acrylate repeating unit (B) having a terminal hydroxyl group is represented by the following chemical formula 2: [Chemical formula 1] 【Chemistry 10】 In the above formula 1, R 1 is a hydrogen atom or a methyl group, R 2 represents a linear or branched alkyl group having 1 to 12 carbon atoms, n represents the number of repeating units (A) and is an integer of 450 to 850, [Chemical formula 2] 【Chemistry 11】 In the above formula 2, R 3 is a hydrogen atom or a methyl group, R 4 represents a straight-chain or branched-chain alkyl group having 1 to 9 carbon atoms to which a hydroxy group is bonded; m represents the number of repetitions of the repeating unit (B) and is an integer of 200 to 350.
5. 2. The unit cell according to claim 1, wherein the weight average molecular weight (Mw) of the copolymer is 120,000 to 140,000.
6. The two or more repeating units (A) include at least one acrylate repeating unit and at least another methacrylate repeating unit, 2. The unit cell according to claim 1, wherein the acrylate repeating unit has an end connected to an alkyl group having a larger number of carbon atoms than the methacrylate repeating unit.
7. The acrylate repeating unit has a terminal end to which a linear or branched alkyl group having 4 to 12 carbon atoms is bonded, 7. The unit cell according to claim 6, wherein the methacrylate repeating unit has an alkyl group having 1 to 3 carbon atoms bonded to an end thereof.
8. the two or more repeating units (A) are all acrylate repeating units, 2. The unit cell of claim 1, wherein at least one of the repeating units (A) is an isobornyl acrylate-based repeating unit.
9. 2. The unit cell of claim 1, wherein the two or more kinds of repeating units (A) include a methyl methacrylate-based repeating unit and a 2-ethylhexyl acrylate (2-EHA)-based repeating unit.
10. 2. The unit cell of claim 1, wherein the (meth)acrylate-based repeat unit (B) having a terminal hydroxy group comprises a 2-hydroxyethyl acrylate (2-HEA)-based repeat unit.
11. 2. The unit cell of claim 1, wherein the additive has a glass transition temperature (Tg) of −10 degrees Celsius or less.
12. The HSP (hilderbrand solubility) of the additive is 19 to 22 (MPa) 0.5 2. The unit cell of claim 1 having a value of
13. 10. The unit cell of claim 1, wherein the adhesive composition comprises 30% to 50% by weight of the copolymer and 50% to 70% by weight of the additive.
14. 2. The unit cell of claim 1, wherein the adhesive composition has a glass transition temperature of −40 degrees Celsius or lower.
15. 2. The unit cell of claim 1, wherein the adhesive composition has a glass transition temperature of −50 degrees Celsius or lower.
16. 10. The unit cell of claim 1, wherein the adhesive composition has a viscosity of 2200 cPs to 2500 cPs at 80°C.
17. 10. The unit cell of claim 1, wherein the adhesive composition has a viscosity of 2200 cPs to 2400 cPs at 80°C.
18. The adhesive strength of the adhesive composition is 40 gf / mm 2 The unit cell of claim 1 .
19. The adhesive strength of the adhesive composition is 85 to 92 gf / mm 2 2. The unit cell of claim 1 ,
20. 20. An electrode assembly formed by alternately stacking the unit cells according to claim 1, The adhesive for bonding the electrodes and the separator includes an adhesive pattern disposed at the same position between the electrodes and the separator.
21. 20. An electrode assembly formed by alternately stacking the unit cells according to claim 1, The adhesive for bonding the electrodes and the separator includes adhesive patterns arranged in an alternating pattern between the electrodes and the separator.
22. A battery cell comprising the unit cell according to any one of claims 1 to 19.
23. 23. The battery cell of claim 22, wherein the separator is folded to have a zigzag configuration.
Citation Information
Patent Citations
Li battery stack consisting of alternately stacked and fixed separators and electrodes
JP2009508298A
Electrochemical element including adhesive bonding composite material between electrode and separator
JP2010514112A
Adhesive composition
JP2014108968A